PENDIDIKAN KEWIRAUSAHAAN BERWAWASAN GENDER BAGI PENGELOLA UNIT USAHA BUMDES DESA KARANG BUNGA, KECAMATAN MANDASTANA, KABUPATEN BATOLA-KALSEL - Nurhikmah Nurhikmah; Devi Rusvitawati; Firda Rezky Heryawan; Chumaidi Chumaidi; Mia Mia; Tiara Agustina (Bakti Banua : Jurnal Pengabdian Kepada Masyarakat, 2020)
A Gender-Based Entrepreneurship Education for BUMDes administrators of Karang Bunga Village, Mandastana District, Barito Kuala in South Kalimantan. This  activity aims to build the community empowerment, especially women in the economic field through the growth and development of skills activities so that they have the ability and competitiveness in employment and economic ventures. The PRA (Participatory Rulai Apraisah) method had been used in implementing this activity. The results reveal that some people of Karang Bunga Village, Mandastana District, Barito Kuala in South Kalimantan, especially women have basic skills about entrepreneurship as the basic capital to find work or open a new business, and there is a community formation to open new businesses based on local potentials with a gender perspective.